Melon jam. Rules of transportation, acceptance, storage of raw materials and auxiliary materials. Ways of waste utilization - Rudakova, A. (ТДАТУ, 2021)
Therefore, the shelf life of the jam from the date of manufacture is sterilized 24 months; not sterilized - 12 months. Transportation must be carried out by all modes of transport in accordance with the rules of transport organizations for the carriage of goods operating on the specified mode of transport. The integrity of the jam must not be damaged during transportation.
Keywords: Jam; benefits of jam